2011
DOI: 10.4172/2157-7633.1000112
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Stem cell Research & Their Role in Various Diseases

Abstract: Stem cells likely play key roles in the repair of diverse injuries or disorders in body. Recent advances in biotechnology and regenerative medicine brought a revolutionary change in the practice of medicine. Advancements in stem cell biology, including embryonic and postnatal somatic stem cells, have made the prospect of tissue regeneration a potential clinical reality. Absolute concept for the use of stem cells in bone disorders has been centered on the strategies for reconstructing segmental regions of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Stem cells (SCs) field of research, named "regenerative medicine, " has emerged rapidly with huge interest among scientists and clinicians [5]. Stem cell therapy can be mediated by a direct contribution to the functional hepatocyte population with embryonic, induced pluripotent, or adult stem cells (ASCs) or by promotion of endogenous regenerative processes through the bone marrow (BM)-derived SCs [6]. SCs are unspecialized cells with an extraordinary ability to self-renew, capable of differentiating into one or more specialized cell types playing a crucial role in homeostasis and tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells (SCs) field of research, named "regenerative medicine, " has emerged rapidly with huge interest among scientists and clinicians [5]. Stem cell therapy can be mediated by a direct contribution to the functional hepatocyte population with embryonic, induced pluripotent, or adult stem cells (ASCs) or by promotion of endogenous regenerative processes through the bone marrow (BM)-derived SCs [6]. SCs are unspecialized cells with an extraordinary ability to self-renew, capable of differentiating into one or more specialized cell types playing a crucial role in homeostasis and tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…A multipotent cell could be further differentiated into various but limited cell types, while a pluripotent cell could be differentiated into any desired cell type ( Figure 1). This process holds great promise for biomedical applications to use it as a potential treatment for human diseases and study cellular pathology in the cell culture dish [1][2][3][4][5][6][7][8]. Studies demonstrated that differentiated cells can be reprogrammed to an embryonic-like pluripotent state [9] or a multipotent state [10][11][12] and by that generated a lot of interest in understanding the molecular basis of cell fate determination and developmental biology.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, stem cells must be identified prospectively & purified carefully in order to study their properties [6]. Human stem cell research holds an enormous potential to contribute the understanding of fundamental human biology [7]. Because of their ability stem cells can differentiate into any tissue type, they have huge potential in various disease therapies and traumatic injuries [8].…”
Section: Introductionmentioning
confidence: 99%